Liberalisasi Penjaringan Mahasiswa Baru di Perguruan Tinggi Keagamaan Islam Negeri: Tantangan dan Peluang - Binti Nasukah; Endah Winarti; Fatimah Fatimah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
The government seeks to liberalize higher education by encouraging the realization of higher education management autonomy. To be independent, universities carry out liberalization through the selection of new students. The emergence of the phenomenon of several allegations of new student admissions provides opportunities for liberalization policies in recruiting new students that have excesses that need to be studied for opportunities and challenges for PTKIN, which is identical to the mission of da'wah. For this reason, it seeks to discuss the liberalization policy in the selection of new students in terms of (1) the forms of legal policy; (2) the challenges of negative excess (3) and the opportunities for advancement for PTKIN. The research uses qualitative methods, through a literature study approach, by collecting secondary data in the form of relevant documents to answer research questions. The results of the study indicate that (1) the Indonesian government has liberalized higher education, in the form of a higher education autonomy policy, in which each institution is given wider authority to obtain funding from the public through the selection of new students. (2) In practice, liberalization in the selection of new students poses negative excess challenges: Increasing education funding by the poor; being stuck in the material-oriented corporate paradigm; Falling into the behavior of corruption, collusion, and nepotism. (3) Liberalization provides opportunities for progress for PTKIN to optimize the role of education financing by the community; The diversity of PTKIN student backgrounds; the Opportunity to build a humanist and fair PTKIN. Practically, the three points of the research findings imply that in implementing the new student recruitment policy, PTKIN can direct the policy to build PTKIN priorities that are humanist and just by avoiding the number of negative excesses that are not in line with PTKIN's ideology as a da'wah institution.